Rancang Bangun Social Media sebagai Sarana Promosi Pariwisata di NTT Berbasis Web - Alfry Aristo Jansen Sinlae; Tifany Anastasia Antonius (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2019)
Tourist destinations in East Nusa Tenggara (NTT) are no less interesting than other regions in Indonesia. But the number of destinations is not accompanied by maintenance and also maximum promotion from the government. Therefore came the idea to create a web-based social media, to provide accurate updates on tourist destinations and maximize the existing promotion system. This system is designed to build using the Bootstrap framework and the system development method used by Waterfall. With the establishment of the NTT Kaliling website with the concept of social media, it can be concluded that this website can provide more extensive and interesting information to be used as a means of promoting NTT tourism by its users.